Diuron lacks promoting potential in a rat liver bioassay - Grassi, Tony Fernando [UNESP]; Tararam, Cibele Aparecida [UNESP]; Spinardi-Barbisan, Ana Locia Tom [UNESP]; Domingues, Maria Aparecida Custódio [UNESP]; Camargo, João Lauro Viana de [UNESP]; Barbisan, Luis Fernando [UNESP] (Taylor & Francis Inc, 2007)
The promoting activity of the herbicide Diuron was evaluated in a medium-term rat liver carcinogenesis bioassay that uses as endpoint immunohistochemically identified glutathione S-transferase positive (GST-P+) foci. Male Wistar rats were allocated to the following groups: G1 to G6 were initiated for liver carcinogenesis by a single dose of diethylnitrosamine (DEN, 200 mg/kg) while groups G7 and G8 received only 0.9% NaCl (DEN vehicle). From the 2nd week animals were fed a basal diet (G1 and G7) or a diet added with Diuron at 125, 500, 1250, 2500 and 2500 ppm (G2 to G5 and G8, respectively) or 200 ppm Hexaclorobenzene (HCB; G6). The animals were submitted to 70% partial hepatectomy at the 3rd week and sacrificed at the 8th week. The herbicide did not alter ALT or creatinine serum levels. No conspicuous GST-P+ foci development was registered in non-initiated rats fed Diuron at 2500 ppm. While DEN-initiated animals fed Diuron at 1250 or 2500 ppm developed mild centrilobular hypertrophy, DEN-initiated HCB-fed animals showed severe liver centrilobular hypertrophy and significant GST-P+ foci development. These findings indicate that the medium-term assay adopted in this study does not reveal any liver carcinogenesis initiating or promoting potential of Diuron in the rat.
Keywords: pesticides; chemical hepatocarcinogenesis; GST-P positive foci; diuron; rats